Blood Health Indicators Changes Induced by Replacing Fish meal with Lentil seed meal in the Common Carp (Cyprinus carpio L.) - Hassan, Bakhan Rafiq; Abdulrahman, Nasreen Mohialddin; Ahmad, Vian Muhamad; Abdulla, Zaweta Sharif (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
According to the research, substituting a fish meal with a plant protein source in a fish diet presents several difficulties. As a result, the goal of this study was to evaluate the effects of substituting lentil seed meal meal for fish meal in the diet of Cyprinus carpio using a variety of blood health indices. Five different diets were created by replacing FM with 0 (control), 5, 10, 15, and 20% lentil seed meal meal. A total of 150 common carp with an initial weight of 103.8±0.5g are randomly distributed into 15 tanks for 70 days, at a rate of 3% live weight per day and two times each day. Blood samples were obtained from five fish in each tank at the end of the feeding trial to analyze hematological and biochemical parameters. Hematological and differential leukocyte counts showed no significant changes (p<0.05). Also, dietary treatments had no effect on serum glucose and total proteins (Albumin and Globulin). However, serum enzyme activity (alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP)), triglycerides, and total cholesterol were increased significantly (p<0.05) as the amount of lentil seed meal meal in the diet grew. According to the findings of this study, the maximum amounts of lentil seed meal replacement in Cyprinus carpio diets might be between 15 and 20% of total protein sources without causing adverse effects on hematological and certain plasma biochemical markers. ?Keywords: Biochemical, Common Carp, Hematology, Plant Protein